Expanding TREC and KREC Utility in Primary Immunodeficiency Diseases Diagnosis - Korsunskiy, Ilya; Blyuss, Oleg; Gordukova, Maria; Davydova, Natalia; Zaikin, Alexey; Zinovieva, Natalia; Zimin, Sergey; Molchanov, Robert; Salpagarova, Aminat; Eremeeva, Alina; Filipenko, Maxim; Prodeus, Andrey; et al. (Frontiers in Immunology, 2020)
Primary immunodeficiency diseases (PID) is a heterogeneous group of disorders caused by genetic defects of the immune system, which manifests clinically as recurrent infections, autoimmune diseases or malignancies. Early detection of PID remains a challenge, particularly in older children with milder and less specific symptoms. This study aimed to assess TREC and KREC diagnostic ability in PID. We carried out analysis of data from children assessed by clinical immunologists at Speransky Children’s Hospital, Moscow, Russia with suspected immunodeficiencies between May 2013 and August 2016. Peripheral blood samples were sent for TREC/KREC, flow cytometry (CD3, CD4, CD8 and CD19), IgA and IgG analysis. A total of 434 children (189 healthy, 97 with group I and II PID (combined T and B cell immunodeficiencies & well-defined syndromes with immunodeficiency) and 148 group III PID (predominantly antibody deficiencies)) were included. Area under the curve (AUC) for TREC in PID groups I and II diagnosis reached 0.82 (CI = 0.75 – 0.90), with best model providing sensitivity of 65% and specificity of 92%. Neither TREC, nor KREC had added value in PID group III diagnosis. In this study, we examined the predictive value of TREC and KREC in PID diagnosis. We found that the TREC had good diagnostic utility for groups I and II PID. Further investigations on a larger cohort are needed to evaluate TREC/KREC abilities to be used as a diagnostic tool on a wider scale.